Sensitivity of Alpine3D modeled snow cover to modifications in DEM resolution, station coverage and meteorological input quantities. (September 2016) - Schlögl, S.; Marty, C.; Bavay, M.; Lehning, M.
Abstract: This study presents a comprehensive sensitivity and uncertainty assessment of important input parameters on the Alpine3D modeled snow water equivalent (SWE) for two different alpine catchments. Horizontal resolution of the DEM grid, station coverage and several meteorological input quantities were modified. Decreasing the horizontal resolution from 25 m to 1000 m leads to a 10% higher SWE. Modifications in the spatial coverage of meteorological stations influences the SWE up to 20%. Modifications of meteorological input quantities within some plausible ranges lead to changes in SWE up to 30%. The results demonstrate that Alpine3D input uncertainties are in general in the same range as the typical measurement uncertainty of SWE and the uncertainty of the typical scenario spread of GCM-RCM ensemble runs. Highlights: Modifications of meteorological input quantities lead to changes in SWE up to 30%. Alpine3D input uncertainties are in general in the same range as the typical measurement uncertainty of SWE.